Socio-economic and demographic patterns of mental health complaints among the employed adults in Estonia - Rainer Reile (Public Library of Science (PLoS), 2021)
Background Mental health problems follow a distinct socio-economic gradient and contribute to the health inequalities. The study aims to analyse the socio-economic and demographic factors of self-reported mental health complaints (stress, depressiveness, overtiredness, suicidal thoughts) among employed adult population in Estonia. Methods Data on 4041 employed respondents (2064 men and 1977 women) aged 20–64 years from nationally representative health surveys from years 2016 and 2018 in Estonia were used for the study. Dependent variables included self-reported stress, depressiveness, overtiredness, and suicidal thoughts. Descriptive statistics and both log-binomial and Poisson regression analysis were used to describe the socio-economic and demographic variations in these mental health complaints. Results More than half of the respondents had either stress, depressiveness, overtiredness or suicidal thoughts with 25% reporting two or more of mental health complaints. Lower personal income was associated with higher rates of all mental health complaints (stress, depressiveness, overtiredness, and suicidal thoughts) among employed adults in Estonia. Additionally, lower education was associated with higher prevalence of depressiveness and lower job skills predicted higher prevalence of suicidal thoughts. Higher prevalence ratios for depressiveness and overtiredness were found for women compared to men whereas Estonians had higher prevalence ratios for stress and suicidal thoughts compared to non-Estonians. All mental health complaints were more frequently reported at younger ages (compared to 50-64-year olds) and by not married or cohabiting respondents. Conclusion High prevalence of mental health complaints and their socio-economic and demographic patterning refer to considerable inequalities in mental health among employed adults. Policy actions targeting especially younger adults and those with financial difficulties are needed to address these early manifestations of mental health problems.